Analysis And Strategies for Strengthening Internal Controls Over Financial Reporting (PIPK) at PT Wika - Belgina Saurmauli, Christine; Rahmayanti, Krisna Puji (Journal Research of Social Science, Economics, and Management, 2026)
Quality financial statements are very important for companies because they are directly related to stakeholder trust, access to funding, and the legitimacy of corporate governance. Internal Control over Financial Reporting (ICFR) is designed to provide reasonable assurance that financial statements are prepared in accordance with generally accepted accounting principles and are free from material errors or fraud. This article aims to analyze the implementation of ICFR at PT WIKA using the COSO Internal Control–Integrated Framework 2013 and the SOE ICFR policy, as well as to identify control weaknesses and strengthening strategies. This research uses secondary data in the form of PT WIKA’s financial statements, ICFR policies, SOE governance documents, and other relevant supporting documents. The method used is a case study with a descriptivequalitative approach through an analysis of the suitability of company practices with the COSO framework and the stages of ICFR implementation. The results of the analysis show that although PT WIKA already has a formal foundation for ICFR through its governance structure, COSO adoption, and ERP-based IT support, its implementation has not been effective due to weaknesses in liquidity risk assessment, revenue and receivables control activities, control documentation and testing, and the low transparency of material deficiency disclosures. Conceptually, this article emphasizes the importance of consistency between the design and implementation of ICFR in the high-risk construction sector, while practically providing recommendations for strengthening policies, processes, human resources, and information systems as the basis for improving governance and restoring stakeholder trust.